2015
DOI: 10.1186/s13059-015-0853-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of RNA-seq expression data across species, tissues and studies

Abstract: BackgroundDifferences in gene expression drive phenotypic differences between species, yet major organs and tissues generally have conserved gene expression programs. Several comparative transcriptomic studies have observed greater similarity in gene expression between homologous tissues from different vertebrate species than between diverse tissues of the same species. However, a recent study by Lin and colleagues reached the opposite conclusion. These studies differed in the species and tissues analyzed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(140 citation statements)
references
References 20 publications
12
125
3
Order By: Relevance
“…However, expression pattern clustering analysis grouped RNA-seq samples according to the study of origin, even when considering the same samples that were separately sequenced and analyzed independently by different groups (S1 Fig), thus arguing against co-analysis of RNA-seq data generated by different protocols. Hence, although Sudmant et al [27] recently showed that differences in gene expression patterns between tissues are greater than are differences between studies, our results reveal that while focusing on a single tissue, differences in gene expression patterns between studies exceeds differences among individuals. Therefore, to avoid such artifacts, we focused our analysis on the largest of the relevant studies, encompassing 462 publicly available RNA-seq samples from Caucasians and sub-Saharan Africans [26], all part of the 1000 Genomes Project [32].…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…However, expression pattern clustering analysis grouped RNA-seq samples according to the study of origin, even when considering the same samples that were separately sequenced and analyzed independently by different groups (S1 Fig), thus arguing against co-analysis of RNA-seq data generated by different protocols. Hence, although Sudmant et al [27] recently showed that differences in gene expression patterns between tissues are greater than are differences between studies, our results reveal that while focusing on a single tissue, differences in gene expression patterns between studies exceeds differences among individuals. Therefore, to avoid such artifacts, we focused our analysis on the largest of the relevant studies, encompassing 462 publicly available RNA-seq samples from Caucasians and sub-Saharan Africans [26], all part of the 1000 Genomes Project [32].…”
Section: Resultscontrasting
confidence: 78%
“…Levels of gene expression can vary among individuals, tissues and species [27]. As such, we utilized RNA-seq experiments to assess differential mitochondrial gene expression patterns among individuals and ethnicities (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we opted to generate gold standard datasets for mouse, rat, and pig through orthology-based transfer of the human tissue annotations, under the assumption that a large portion of orthologous genes are similarly expressed in homologous tissues across mammals (3147). …”
Section: Methodsmentioning
confidence: 99%
“…Recently, a meta-analysis of RNA-Seq expression data across various species, tissues, and studies was performed 10 ; however, the interpretation of such data is difficult. Biologists are often at a loss because of the sheer number of datasets in public databases provided by numerous researchers.…”
Section: Introductionmentioning
confidence: 99%